Affirmative action, principles of justice, and the evolution of urban theory - Schumaker, Paul; Kelly, Marisa (1999)
Analysis of interviews with 112 elected officials in 12 American cities indicates that their support for affirmative action is more strongly influenced by the justice principles they hold than by the contextual variables normally emphasized by leading urban paradigms. Allegiance to fair equal opportunity and blocking cumulative inequalities enhances support for affirmative action, whereas allegiance to maximizing aggregate utility and retaining market allocations reduces such support. These results suggest that urban paradigms should include the moral principles of participants as well as variables describing the interests that officials represent and the economic, social, political, and cultural contexts that constrain their decisions. - Reproduced
Keywords: Urban development